Where have all the bishops gone? - J. E. Wehrmeyer (Acta Theologica)
This paper investigates how the Greek term episkopo`~ and its related variants are translated in English Bible translations. From early translations to the middle of the 20th century, “bishop” was the preferred translation equivalent. However, translations done in the latter half of the 20th century prefer the more generic term “overseer” or a functional equivalent. This apparent neutrality in selecting a more general term has, however, theological implications and may actually violate the principle of sola scriptura. The paper shows that the New Testament episkopo`~ functions as a term with meanings similar to its secular use in ancient times as well as its use in the Septuagint. It is suggested that the term boldly declares the colonisation of the kingdoms of men by the kingdom of God. Therefore the translation equivalent also needs to be a term with equivalent semantic content.